The bookshelf of the University library in Pula is (no longer) the last station of the travel - Frančić, Damjana (Array, 2019)
When arriving by train from the North to Istria, the last stop is the railway station in Pula, so the Library is the last station for travel books. We searched our fund for the travelogues exhibition and found that we have very little travelogues about Istria, and disproportionately more travelogues about distant parts of the world. The catalogs of other libraries in Europe and the world show many travel books about Istria, which are digitalised and now can be read on the internet.